Functional and disordered meso-macroporous gamma-Al2-xMxO3 +/- y (M = Cu and/or Ce) - Gnanakumar, Edwin S.; John, Jino C.; Raja, Thirumalaiswamy; Gopinath, Chinnakonda S. (Journal of Nanoscience and Nanotechnology, 2013)
Disordered meso-macro porous Cu-Ce-Al2O3 nanocomposite (gamma-Al2-xMxO3 +/- y, M = Cu and or Ce) with different compositions has been synthesized. In situ templated sol-gel method has been adopted with simple EDTA ethylenediamine tetra aceticacid and ethylenediamine molecules to prepare gamma-Al2-xMxO3 +/- y, (M = Cu and or Ce). Above meso-macro porous materials were characterized by structural, spectroscopy, microscopy and textural techniques. Detailed characterization indicates that Cu2+ ions are introduced into the ceria and alumina lattice positions. Nano composite nature of the gamma-Al2-xMxO3 +/- y has been confirmed by detailed microscopy investigations. Catalytic activity of the above nanocomposite materials have been screened for environmentally important CO oxidation reaction. 30% Ce-60% Al and 10% Cu containing material shows the best activity among other meso-nnacroporous material with (50%) 100% CO oxidation at (107 degrees C) 145 degrees C.
Keywords: Alumina; CO oxidation; heterogeneous catalysis; Meso-Macroporous Material; Nanocomposite; Sol-gel synthesis

Chemically doped perylene diimide lamellae based field effect transistor with low operating voltage and high charge carrier mobility - Arulkashmir, Arulraj; Jain, Bhanprakash; John, Jino C.; Roy, Kanak; Krishnamoorthy, Kothandam (Chemical Communications, 2014)
Chemical doping of an electron transporter results in the formation of a radical anion containing semiconductor which showed high electron mobility (13 cm(2) V-1 s(-1)) at low operating voltage (1 V).